Specific adsorption of some complement activation proteins to polysulfone dialysis membranes during hemodialysis - Mares, Jan; Thongboonkerd, Visith; Tuma, Zdenek; Moravec, Jiri; Matejovic, Martin (Kidney international, 2009)
Dialyser bioincompatibility is an important factor contributing to complications of hemodialysis with well known systemic consequences. Here we studied the local processes that occur on dialysis membranes by eluting proteins adsorbed to the polysulfone dialyser membranes of 5 patients after 3 consecutive routine maintenance hemodialysis sessions. At the end of each procedure, a plasma sample was also collected. These eluates and their accompanying plasma samples were separated by 2-dimensional gel electrophoresis; all proteins that were present in all patients were analyzed by tandem mass spectrometry; and a ratio of the relative spot intensity of the eluate to plasma was calculated. Of 153 proteins detected, 84 were found in all patients, 57 of which were successfully identified by mass spectrometry as 38 components of 23 unique proteins. In 10 spots the relative eluate intensity differed significantly from that in the plasma, implying preferential adsorption. These proteins included ficolin-2, clusterin, complement C3c fragment, and apolipoprotein A1. Our finding of a selective binding of ficolin-2 to polysulfone membranes suggests a possible role of the lectin complement pathway in blood-dialyser interactions.
Keywords: Complement System Proteins; Clusterin; Renal Dialysis; apolipoprotein A-I; dialýza ledvin; Apolipoprotein A-I; Adsorption; klusterin; Lectins; Polymers; sulfony; lidé; Ficolins; fikoliny; membrány umělé; Sulfones; Complement C3c; Aged, 80 and over; hmotnostní spektrometrie; Membranes, Artificial; lektiny; Aged; polymery; Mass Spectrometry; lidé středního věku; senioři nad 80 let; senioři; komplement C3c; Middle Aged; komplement; adsorpce; Humans